REMOVAL OF COBALT, NICKEL AND CHROMIUM IONS FROM AQUEOUS SOLUTION USING ELECTROSPUN HYBRID 3D GRAPHENE/CELLULOSE ACETATE NANOFIBERS - A/L SUNDERA MURTHE, SATISVAR (2019)
In recent times, heavy metal contamination of groundwater has become a serious global threat for human beings in securing clean potable water. The presence of heavy metal in water leads to a myriad of health related issues such as kidney damage, neurological damage, lung disease, heart disease, cancer and even death